Dynamic Architecture for Analytical Its Services - Michal Zabovsky; Matus Chochlik; Karol Matiasko; Eva Valentikova (Communications - Scientific letters of the University of Zilina, 2010)
The emergence of various technologies allowing the real-time collection, processing and transfer of data between stationary traffic devices, moving vehicles and data centers provides many new possibilities for Intelligent Transportation Systems (ITS). However, the need for mobile access to analytical data leads to problems with mobile computers connectivity. Mobile computers often suffer from limited connectivity or lack of network access. Existing data replication solutions are not well suited for mobile scenarios as well as algorithms used for data replication, in spite of the fact that it is the most desirable environment. In the following paper we introduce the algorithm for analytical data replication forming dynamic architecture including mobile computers connected by wireless network based on IEEE 802.11.